The role of the service manager's perceived career success in frontline employees’ learning processes and service improvement - Jong, Ad de (2021)
Previous literature fails to offer firms consistent guidelines on how successful managers may enhance or reduce the potential to learn from frontline service encounters. In addressing this research gap, this study contributes to the frontline employee (FLE) literature by 1) investigating the contingency role of managers’ perceived career success in FLEs’ personal learning process, 2) distinguishing between FLEs’ service-related and context-related personal learning, and 3) accounting for both exploratory and exploitative learning. This study uses two datasets: an exploratory dataset on 253 FLEs and a multilevel and multisource dataset on 444 FLEs and 55 service managers. Findings reveal that managers who are unsuccessful in their careers still stimulate frontline learning processes, but their subordinates generally use only their service-related personal learning to generate ideas for service improvement. Successful managers are better able to guide their FLEs in how to turn context-related learning into service improvement.